Implementation of the Merah Putih Cooperative Policy in Supporting the Free Nutritious Food Programme for School Students - Rahmina, Raja Enkla Kurniadinta Putri; Anggraini, Rendyta (Journal Governance Bureaucratic Review, 2026)
This study aims to analyse the implementation of the Koperasi Merah Putih (KMP) policy as an actor in supporting the programme to provide free nutritious meals for school students in Tanjungpinang City. Koperasi Merah Putih, which was formed with a spirit of multi-stakeholder collaboration, is believed to play an important role in the food supply chain and logistics distribution, thereby ensuring the effectiveness and sustainability of the programme. Using a qualitative approach with case studies, this study focuses on the implementation model of (George C. Edwards III: 1980) Communication, Resources, Disposition, and Bureaucratic Structure.  Data was collected through in-depth interviews with the management of the Merah Putih Cooperative, school principals, and representatives from the Education Office and the Cooperative Office. The results show that the implementation of this policy faces major challenges in terms of resources, particularly the availability of working capital and efficient supply chain management capabilities, as well as land for the Merah Putih Cooperative office. Several areas of Tanjungpinang City face difficulties in land management and the cooperative's business activities. On the other hand, communication and the disposition of actors show high levels of support. Koperasi Merah Putih has succeeded in reducing logistics costs and improving the quality of raw materials, but the scalability of the programme still requires more integrated administrative and budgetary support from the Tanjungpinang City Government. This study recommends the need to strengthen the supporting bureaucratic structure and increase the capacity of Koperasi Merah Putih   through modern management training to achieve optimal public policy effectiveness in supporting the free nutritious meal programme.